IKLAN TELEVISI DALAM PERSEPSI KOMUNIKAN - Deddi Duto Hartanto (Jurnal Desain Komunikasi Visual Nirmana, 2000)
Private televisions have taken a role in the fast growing of advertising world in Indonesia. The ascent of the private televisions with their commercial programs has shifted the position of printed and radio commercials. All programs in the television such as entertaintment%2C news%2C movies%2C quizzes%2C etc. are inseparable with TV commercials. Through these commercials%2C advertising producers and their creative team expect their commercials%2C advertising producers and their creative team expect their works perceived by the public. accordingly%2C TV commercial creators should give a clear perception of the ad they made. Abstract in Bahasa Indonesia : Berkembang pesatnya dunia periklanan di Indonesia tidak terlepas dari peranan televisi swasta. Munculnya televisi swasta dengan iklan televisinya berhasil menggeser posisi iklan media cetak dan radio. Setiap tayangan hiburan%2C informasi%2C film%2C kuis dan lain-lain tidak bisa dipisahkan dari iklan. Melalui iklan televisi ini%2C para produsen dan kreator iklan berharap hasil karyanya dapat diterima komunikan. Untuk itu kreator iklan. harus dapat memberikan persepsi yang jelas tentang iklan yang dibuatnya. tv commercials%2C advertisement perception.